Pengelolaan Wisata Mangrove Berbasis Partisipasi Masyarakat di Desa Marannu - F Fitrawahyudi; Muhammad Nasrum; S Sofyan (Universitas Muhammadiyah Parepare)
The general problems found in the program partners were the lack of community participation in development, the lack of community knowledge and skills in managing natural resources, the lack of comprehension of village governance and tourism managers in utilizing the potential of mangrove tourism villages, and the lack of comprehension of environmental conservation to protect mangrove forest habitats. The solution offered through the KKN-PPM program were to increase community participation through empowering rural communities, especially for women and the elderly widows who are not economically productive institutionalized through the "The Pakatau", efforts to increase the ability of mangrove ecotourism governance were carried out training to increase the capacity of mangrove ecotourism management for village officials and tourism managers. The efforts to increase the human development index in the field of improving the economy, welfare, and health. Therefore efforts were made to increase the knowledge and skills of processing mangrove fruits into superior products of the village and training on environmental preservation of mangrove forests. To achieve those goals, several activities are offered by the KKN-PPM program such as the institutionalized of the community through "The Pakatau" community learning groups, tourism management training for tourism managers, training for making superior village products for women and elderly widows who are not economically productive, and the promotion of environmental preservation and values in interacting with tourists, as well as several other supporting programs. The expected output targets achieved this program such as the increasing of community comprehension and skills, village governance, and tourism managers in managing, processing and maintaining mangrove habitats as a source of income for the community and village.